Germline landscape of RPA1, RPA2 and RPA3 variants in pediatric malignancies: identification of RPA1 as a novel cancer predisposition candidate gene - Sharma, Richa; Oak, Ninad; Chen, Wenan; Gogal, Rose; Kirschner, Martin; Beier, Fabian; Schnieders, Michael J.; Spies, Maria; Nichols, Kim E.; Wlodarski, Marcin (Frontiers in Oncology, 2023)
Replication Protein A (RPA) is single-strand DNA binding protein that plays a key role in the replication and repair of DNA. RPA is a heterotrimer made of 3 subunits -RPA1, RPA2, and RPA3. Germline pathogenic variants affecting RPA1 were recently described in patients with Telomere Biology Disorders (TBD), also known as dyskeratosis congenita or short telomere syndrome. Premature telomere shortening is a hallmark of TBD and results in bone marrow failure and predisposition to hematologic malignancies. Building on the finding that somatic mutations in RPA subunit genes occur in ~1% of cancers, we hypothesized that germline RPA alterations might be enriched in human cancers. Because germline RPA1 mutations are linked to early onset TBD with predisposition to myelodysplastic syndromes, we interrogated pediatric cancer cohorts to define the prevalence and spectrum of rare/novel and putative damaging germline RPA1, RPA2, and RPA3 variants. In this study of 5,993 children with cancer, 75 (1.25%) harbored heterozygous rare (non-cancer population allele frequency (AF) < 0.1%) variants in the RPA heterotrimer genes, of which 51 cases (0.85%) had ultra-rare (AF < 0.005%) or novel variants. Compared with Genome Aggregation Database (gnomAD) non-cancer controls, there was significant enrichment of ultrarare and novel RPA1, but not RPA2 or RPA3, germline variants in our cohort (adjusted p-value < 0.05). Taken together, these findings suggest that germline putative damaging variants affecting RPA1 are found in excess in children with cancer, warranting further investigation into the functional role of these variants in pediatric tumor formation oncogenesis.